Teacher's perceptions related to principals' creative leadership practices towards school effectiveness - Arivayagan, Keetanjaly; Lope Pihie, Zaidatol Akmaliah (Universiti Putra Malaysia Press, 2017)
Recently research in creative leadership has ballooned to encompass the essential qualities in organizational leaders (Petrie, 2014). In this study, Generativity Theory was utilized to explore the concept of creativity in leaders. Epstein (1999) presented four main core skills and abilities that assist people in expressing creativity individually which are capturing, challenging, broadening and surrounding. Model of high performing school by Shannon and Bylsma (2007) was utilized to measure school effectiveness. The purpose of this study is to determine teacher’s perceptions related to principals’ creative leadership practices towards school effectiveness in secondary schools in Klang District. Simple random sampling was used to select ten secondary schools from three different clusters of schools in the Klang District. A total of 250 teachers from these ten schools participated in this study. The study used self-administered questionnaires. The data are collected and analyzed using descriptive statistics (mean, standard deviation) and inferential statistics (Pearson correlation and Multiple Regressions). This research endeavoured to answer the research questions through employing quantitative research method. This study discovered that the level of school effectiveness as practiced by secondary school teachers was overall high level. On the other hand, it was concluded that the level of creative leadership practiced by school leaders is at moderate level. This study also found out a moderate correlation between school principals’ creative leadership practice and school effectiveness (r = .617, p < .01). Additionally, multiple regression analysis indicated creative leadership practices domain; Encourage Capturing received the strongest weight in the prediction (β = 0.383, p <.05). Implications of the findings and recommendations for developing school principals’ creative leadership and school effectiveness are discussed.